Effect of plasma creatin kinase (CK) activity on the results of special ability tests in elite classical style wrestlers - Starosta, W.; Hübner-Wozniak, E. (Biology of Sport, 2005)
The aim of this paper was gaining the knowledge if the creatine kinase activity (CK) in plasma, which is the index of muscle fibres injuries, has some influence on the motor ability tests results. Studies were conducted during a training camp. Eight elite wrestlers took pari in the study and they performed a set of 7 efficiency tests during 2 days. The CK activities were marked in mornings -before tests. The lack of statistically significant correlations between test results, expressed by both - the absolute values an by points " T " scale, and the CK activity in plasma was stated. However, it seems that the efficiency tests, especially those engaging upper limbs and the trunk muscles, should not be conducted during large training loads employment because the tests results might be dependent on the level of disturbances of the muscle fibres homeostasis elicited by performed earlier physical effort.